Tumor Necrosis Factor-Like Weak Inducer of Apoptosis Accelerates the Progression of Renal Fibrosis in Lupus Nephritis by Activating SMAD and p38 MAPK in TGF-β1 Signaling Pathway - Zhiqin Liu; Leixi Xue; Zhichun Liu; Jun Huang; Jian Wen; Ji Hu; Lin Bo; Ru Yang (Hindawi Limited, 2016)
This study aim was to explore the effects of tumor necrosis factor-like weak inducer of apoptosis (TWEAK) in lupus nephritis and its potential underlying mechanisms. MRL/lpr mice were used for in vivo experiments and human proximal tubular cells (HK2 cells) were used for in vitro experiments. Results showed that MRL/lpr mice treated with vehicle solution or LV-Control shRNA displayed significant proteinuria and severe renal histopathological changes. LV-TWEAK-shRNA treatment reversed these changes and decreased renal expressions of TWEAK, TGF-β1, p-p38 MAPK, p-Smad2, COL-1, and α-SMA proteins. In vitro, hTWEAK treatment upregulated the expressions of TGF-β1, p-p38 MAPK, p-SMAD2, α-SMA, and COL-1 proteins in HK2 cells and downregulated the expressions of E-cadherin protein, which were reversed by cotreatment with anti-TWEAK mAb or SB431542 treatment. These findings suggest that TWEAK may contribute to chronic renal changes and renal fibrosis by activating TGF-β1 signaling pathway, and phosphorylation of Smad2 and p38 MAPK proteins was also involved in this signaling pathway.